2019
DOI: 10.1111/adj.12726
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden of acute odontogenic infections: the South Australian experience

Abstract: Background Acute odontogenic infections are a common surgical emergency managed by public hospitals in Australia which cause considerable patient morbidity and occasionally, mortality. Despite posing a significant public health burden, Australian data evaluating the cost of the management of these patients are lacking. This study assessed the patient and treatment variables associated with inpatient management of deep odontogenic infections, and their respective financial impact, at a statewide Oral & Maxillof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…After abscess incision and drainage, patients still need ongoing symptomatic treatment, and long hospitalization times place a heavy burden both on patients and social security. [19][20][21] Our data shows that with an average hospitalization time of 9 days, patients aged >60 years were 3.784 times more likely to have a longer hospitalization than those aged ≤18 years (Table 5), possibly due to age-related changes in patients' health condition. 1,22,23 Older patients with systemic diseases are more likely to obtain poor therapeutic effect, a long treatment cycle, and greater possibility of serious complications.…”
Section: Discussionmentioning
confidence: 79%
“…After abscess incision and drainage, patients still need ongoing symptomatic treatment, and long hospitalization times place a heavy burden both on patients and social security. [19][20][21] Our data shows that with an average hospitalization time of 9 days, patients aged >60 years were 3.784 times more likely to have a longer hospitalization than those aged ≤18 years (Table 5), possibly due to age-related changes in patients' health condition. 1,22,23 Older patients with systemic diseases are more likely to obtain poor therapeutic effect, a long treatment cycle, and greater possibility of serious complications.…”
Section: Discussionmentioning
confidence: 79%
“…-Have they had previous antibiotics and did these follow the guidelines? 12 -Why have they not seen a dentist?…”
Section: Discussionmentioning
confidence: 99%
“…This needs to be compared with the average cost of a single tooth extraction in private dental practice, which is $181 (125 times less expensive). 12…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Western Australia reported that over the 10-year period studied (1999–2009), more than 130,000 adults required hospitalisation for dental conditions at a direct cost of more than AUD 400 million [ 17 ]. A separate report on the financial burden of odontogenic infections showed that 462 cases of dental infections between 2006 and 2014 required hospitalisation, and the average cost per patient was AUD 12,228 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%